Solar Migrating Atmospheric Tides in the Winds of the Polar Region of Venus - Peralta, Javier (2012)
We study the effects of migrating solar tides on the winds at the cloud tops of the polar region of Venus. The winds were measured using cloud tracking on images obtained at wavelengths of 3.9 and 5.0 μm by the instrument VIRTIS-M onboard Venus Express. These wavelengths probe about the same altitude close to the cloud tops, allowing for the first time to retrieve winds simultaneously in the day and nightside of the planet. We use a dataset with observations from 16 orbits, covering a time span of 289 days and a latitude range between 70°S and 85°S, the region where the so called cold collar resides. Diurnal and quarter-diurnal tides (wavenumbers 1 and 4) were detected in the wind field, with a decoupled influence on the zonal and meridional directions. The diurnal tide is the dominant harmonic with amplitudes of about 4.7 m/s exclusively affecting the meridional component of the wind and forcing a solar-to-antisolar circulation at the polar region. The quarter-diurnal mode is only apparent in the zonal wind in a restricted latitude range with amplitudes ∼2.2 m/s. The spatial structure of the diurnal tide has also been investigated, obtaining a vertical wavelength of about 8 km, in accordance with predictions by models. Finally, a theoretical relation between the amplitudes of tidal temperature and tidal wind has been derived and its validity tested with models and results from previous missions.